Sweethearts a novel - Zarr, Sara (New York Little, Brown and Co, 2008)
After losing her soul mate, Cameron, when they were nine, Jennifer, now seventeen, transformed herself from the unpopular fat girl into the beautiful and popular Jenna, but Cameron's unexpected return dredges up memories that cause both social and emotional turmoil
1
NEW, LITERATURE
Keywords: Family problems -- Fiction; Love -- Fiction; Popularity -- Fiction; Psychological abuse -- Fiction; Schools -- Fiction; Self-esteem -- Fiction; Weight control -- Fiction; Utah -- Fiction